Islamic Banking - Mirakhor, Abbas (IMF Working Papers; Working Paper ;, 1991)
Islamic banks are prohibited from charging or paying interest, and thus can operate only on the basis of profit-sharing arrangements. This paper provides a brief survey of the theory and practice of Islamic banking. It covers developments in Islamic banking since the mid-1970s, how such banks operate, and the analytical underpinnings of a financial system based on Islamic principles. Finally, the future of Islamic banking is assessed.